Dimensi Tasawuf dalam Arbain an-Nawawi: Pendidikan Spiritual bagi Generasi Muslim - Muhammad Adib; Hamidah Hamidah; Muhammad Akmansyah (JURNAL AL-QAYYIMAH, 2025)
Spiritual education in Islam plays an important role in individual character building, especially amidst the complex challenges of modern times. This article discusses the integration of Sufism values, such as ikhlas, tawakal, and muraqabah, in spiritual education through an analysis of the hadiths of Arbain an-Nawawi. These hadiths not only provide guidance on worship, but also contain profound teachings of Sufism, which can shape the morals and spirituality of young Muslims. This research uses a qualitative approach with content analysis to explore the meaning and relevance of Sufism values in the context of education. The results show that the application of these values can help students develop a strong character, not only in academic aspects but also in morals and spirituality. Thus, Sufism-based education is expected to create a generation of Muslims who are intelligent, noble, and able to face global challenges with high spiritual depth. This research also suggests the need to develop an Islamic education curriculum that is more integrated with Sufism values to prepare a young generation that is intellectually and spiritually balanced